2013
DOI: 10.1111/ahg.12004
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Set of SNPs for the Noninvasive Prenatal Diagnosis of β‐Thalassaemia

Abstract: Summaryβ-thalassaemia is one of the commonest autosomal recessive single-gene disorders worldwide. Prenatal tests use invasive methods, posing a risk for the pregnancy itself. Development of a noninvasive prenatal diagnostic method is, therefore, of paramount importance. The aim of the present study is to identify high-heterozygote informative single-nucleotide polymorphisms (SNPs), suitable for the development of noninvasive prenatal diagnosis (NIPD) of β-thalassaemia. SNP genotyping analysis was performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The results of this study revealed that, 72.28% of couples eligible for qualitative SNPs based NIDP, 92% are quantitative detection. They believe that this method is sensitive and specific for detection of paternally inherited mutation in maternal plasma 40 .…”
Section: Warunee Et Al Established Nipd For Identifyingmentioning
confidence: 99%
“…The results of this study revealed that, 72.28% of couples eligible for qualitative SNPs based NIDP, 92% are quantitative detection. They believe that this method is sensitive and specific for detection of paternally inherited mutation in maternal plasma 40 .…”
Section: Warunee Et Al Established Nipd For Identifyingmentioning
confidence: 99%
“…SNPs rs968857_3 0 cb and rs7480526_II74 were selected after a genotyping analysis carried out in a previous study, 26 whereas SNPs rs10768683_AvaII and rs3834466_IIe are routinely used in Cyprus for prenatal diagnosis. 27 Two of the SNPs are located within the b-globin gene and the other two SNPs 5 0 to the d-globin gene, therefore, any recombination events would be instantly recognisable.…”
Section: Selection Of Snps and Primer Designmentioning
confidence: 99%
“…26 SNPs were considered informative when the mother was homozygous and the father was heterozygous for the same SNP. Ten families having at least two informative SNPs of the four analysed above were selected for the NGS analysis.…”
Section: Family Studymentioning
confidence: 99%
“…Invasive prenatal diagnosis (IPD) for pregnancies at risk of a haemoglobinopathy can be offered, but due to a procedure‐related risk of miscarriage of 0.1–0.2%, non‐invasive prenatal diagnosis (NIPD) without risk of pregnancy loss is preferable. Following the discovery of cell‐free fetal DNA (cffDNA) in maternal plasma, many studies have been conducted using this source of genetic material to develop NIPD for β ‐thalassaemia . Most focus on detecting inheritance of paternal mutations when parents carry different mutations .…”
Section: Introductionmentioning
confidence: 99%